Pemetaan Deforestasi dan Perubahan Tutupan Lahan di Wilayah Pertambangan Nikel Kecamatan Pomalaa Memanfaatkan Teknologi Penginderaan Jauh - Andi Baso Sofyan A. P.; Feri Fadlin; Dawamul Arifin; Radik Khairil Insanu; Ahmad Aris Mundir Sutaji (Geomatics Technology Study Program, Politeknik Pertanian Negeri Samarinda, 2024)
Pomalaa District, Kolaka Regency, Southeast Sulawesi Province, is one of the regions in Indonesia which has quite large mining potential, especially for nickel commodities. The stages of nickel mining activities consist of land clearing activities which can cause deforestation or reduction of forest area. The aim of this research is to map deforestation and land cover changes that occur in the nickel mining area of Pomalaa District. It is expected that the results of this research can be used as consideration in formulating policies for efforts to rehabilitate land damaged by mining activities in Pomalaa District, Kolaka Regency, Southeast Sulawesi Province. The method used in this research is multi-time remote sensing image data analysis. The data used are Landsat 8 images in 2014, 2018 and 2023 to analyze changes in forest areas and changes in land cover at the research location during that time period. The results of the research show that there has been a decrease in the area of forest and vegetated areas, that is in 2014 the area reached 17,207.9 hectares to 16,178.4 hectares in 2018 and 16,110.1 hectares in 2023. Meanwhile, the mine excavation area has increased from 1,792.3 hectares in 2014 to 2,005.4 hectares in 2023. Likewise, the area of built-up land and open land has increased from 3,509.3 hectares in 2014 to 4,370.7 hectares in 2023.